Scoring Models in Finance - Rychnovský, Michal; Zouhar, Jan, 1982-; Kalčevová, Jana; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
The aim of the present work is to describe the application of the logistic regression model to the field of probability of default modeling, and provide a brief introduction to the scoring development process used in financial practice. We start by introducing the theoretical background of the logistic regression model; followed by a consequent derivation of three most common scoring models. Then we present a formal definition of the Gini coefficient as a diversification power measure and derive the Somers-type formulas for its estimation. Finally, the key part of this work gives an overview of the whole scoring development process illustrated on the examples of real business data.
Vedoucí práce: Jan Zouhar
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor dipl. práce]; diplomové práce; master's theses